MENIMBANG RELEVANSI PERSEMBAHAN PERSEPULUHAN BERDASARKAN MALEAKHI 3:6-12 DI GPKB WILAYAH IV, KECAMATAN SADANIANG, KABUPATEN MEMPAWAH, KALIMANTAN BARAT - Romelus Blegur; Nico Pabayo Gading; Dinar Br Karo; Nastiti Puspita Rini; Ruslin Ruslin (SAINT PAUL'S REVIEW, 2022)
This study aims to discuss tithing offerings based on the Bible Malachi 3:6-12 to see its relevance to the church today. The research was conducted at GPKB Region IV, Sadaniang District, Mempawah Regency, West Kalimantan. The method used is a biblical hermeneutic method to interpret the biblical text and also a survey method with a quantitative approach. The finding in this study is that, tithing offerings are still relevant today because they are based on the unchanging word of God, legalized by God, and have the nature of continuity that remains a legacy for church practice.